UNIVERSITY STUDENTS' MULTICULTURAL ATTITUDES IN NORTH SUMATRA: Insights for Multicultural Education in Indonesia - OK, Azizah Hanum; Arsyad, Junaidi; Budianti, Yusnaili (Journal of Contemporary Islam and Muslim Societies, 2025)
This study examines the multicultural attitudes of university students in North Sumatra, Indonesia, and explores their implications for advancing multicultural education in higher education. Using a phenomenological case study approach, data were gathered through semi-structured interviews with fifteen students representing diverse ethnic and religious backgrounds. The findings indicate that students consistently demonstrated tolerance, empathy, and appreciation of cultural diversity, but also faced challenges in intercultural communication, particularly due to language differences. These results underscore the urgent need for universities to strengthen multicultural education by addressing linguistic diversity and implementing inclusive pedagogical practices. The novelty of this study lies in its contextual evidence from North Sumatra, which enriches the discourse on multicultural education that has often been dominated by theoretical discussions. Accordingly, this research provides both empirical and practical insights that can inform the development of more inclusive policies and practices in Indonesian higher education.Keywords: Multicultural attitudes, multicultural education, diversity, tolerance